EVALUASI HIBRIDA DAN KEMAMPUAN DAYA GABUNG BEBERAPA GALUR INBRED JAGUNG DI LAHAN MASAM - P.K. DEWI HAYATI; T. PRASETYO; A. SYARIF (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2014)
Planting maize hybrid varieties tolerant to acid soils offers an alternative strategy for improving maize productivity in acid soils. The objectives of this study were to evaluate and select maize hybrids for high yield potential in acid soils. Fifteen single maize hybrids derived from a 6 x 6 diallel cross, six parental inbred lines and two chek varieties were evaluated in Ultisol at UPT Farm, Andalas University. The evaluations were carried out in a RCB design with three replications. Several hybrids had high yielding potential in acidic soils as the hybrids produced higher yield compared to Sukmaraga as a tolerant check variety. The results from combining ability analysis showed the preponderance of non-additive gene actions in the control of yield in acid soils. The hybrids performed high and significant specific combining ability and also higher mid-parent and better parent heterosis, indicating that the heterosis breeding may be rewarding. Hence, it is suggested that these promising hybrids should be further tested before it is released as new hybrid varieties.